Transfection of baboon dendritic cells with plasmid DNA containing HIV-1C genes : effect of transfection methods on antigen processing and presentation to T lymphocytes - Fiff, Fabian (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSCMedSc (Pathology. Medical Virology))--University of Stellenbosch, 2005.